Principles and Perspectives of Healthcare in the Republic of Serbia - Vacić, Nebojša; Momčilović, Ana (Medical Word, 2025)
Health care represents one of the most important segments of the medical profession, and nurses play an irreplaceable role in the health system. Their work includes various aspects of patient care, from basic medical interventions to emotional support and education of patients and their families. A special aspect is the development and improvement of health care after the completion of formal nursing education, which implies continuous learning and improvement, but also accepting new challenges that come with the development of technology and changes in health systems. In this work, the principles of the application of health care in our country are presented, starting from the educational path of nurses and the beginning of their work in health institutions, through the basic principles of care and challenges in everyday practice to the guidelines for future work and the implementation of modern technologies. The role of nurses in the future will be even more significant, because this profession will provide not only technical, but also strategic and leadership competencies that are necessary for a sustainable and quality health system.
Keywords: health care; nurses; education